INNOVATIONS IN THE FOODSERVICE BUSINESS IN LARGE POLISH CITIES - Edyta Gheribi; Gultekin Altuntas; Alessandro Bonadonna (Acta Scientiarum Polonorum. Oeconomia, 2018)
Innovation plays an important role enabling businesses to retain their competitiveness ensuring their longterm survival on dynamic markets. This article presents innovations in terms of an offer (product/services) and/or organizational/marketing process in the foodservice businesses as a competitive factor. The study was carried out using a qualitative, constructivist perspective and a quantitative research method from January to November 2017. Entrepreneurs working in Poland in the foodservice businesses were interviewed as were individual foodservice businesses in Warsaw and Łódź. A total of 70 businesses were studied, 5 chain services and 65 individual restaurants, 40 in Warsaw and 25 in Łódź.